Deployment mode selection and evolution strategy of 5G network - Xu YANG; Ziyu XIAO; Yongping SHAO; Xiaoming SONG (Dianxin kexue)
Standalone (SA) deployment and non-standalone (NSA) deployment are the key issues considered in the early stage of 5G network introduction.Firstly,the deployment architecture options in 3GPP standard were introduced and the key deployment architectures were analyzed and compared.Then two evolution routes of 5G network deployment were put forward.At last,the deployment mode and evolution strategy of 5G core network were given,which provided references for the deployment mode and evolution path selection of 5G network.